2011 Sixth International Conference on Availability, Reliability and Security 2011
DOI: 10.1109/ares.2011.79
|View full text |Cite
|
Sign up to set email alerts
|

Effective Security Impact Analysis with Patterns for Software Enhancement

Abstract: Unlike functional implementations, it is difficult to analyze the impact software enhancements on security. One of the difficulties is identifying the range of effects by new security threats, and the other is developing proper countermeasures. This paper proposes an analysis process that uses two kinds of security pattern: security requirements patterns for identifying threats and security design patterns for identifying countermeasures at an action class level. With these two patterns and the conventional tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The mal-activity diagram 1 [8] in figure 1 describes the expected order and sequence of events which include the user initiated events (white objects) and the attacker/misuser events (black objects) with arrows indicating the flow of activities. It also shows the countermeasures (gray objects) to the identified security threats and the points at which the countermeasures are expected to be applied in order to mitigate the threats appropriately.…”
Section: The "Make Referral" Use Casementioning
confidence: 99%
“…The mal-activity diagram 1 [8] in figure 1 describes the expected order and sequence of events which include the user initiated events (white objects) and the attacker/misuser events (black objects) with arrows indicating the flow of activities. It also shows the countermeasures (gray objects) to the identified security threats and the points at which the countermeasures are expected to be applied in order to mitigate the threats appropriately.…”
Section: The "Make Referral" Use Casementioning
confidence: 99%
“…We describe the process of data extraction of the 10 studies remaining in Section 3. These studies are identified throughout this paper as S1 to S10 as follows: S1 -Adaptive requirement-driven architecture for integrated healthcare systems (Yang et al, 2010) S2 -Analysing security requirements patterns based on problems decomposition and composition (Wen et al, 2011) S3 -An architectural framework of the integrated transportation information service system (Chang and Gan, 2009) S4 -Application of ontologies in identifying requirements patterns in use cases (Couto et al, 2014) S5 -Effective security impact analysis with patterns for software enhancement (Okubo et al, 2011) S6 -From requirement to design patterns for ubiquitous computing applications (Knote et al, 2016) S7 -Modeling design patterns with description logics: A case study (Asnar et al, 2011) S8 -Mutation patterns for temporal requirements of reactive systems (Trakhtenbrot, 2017) S9 -SACS: A pattern language for Safe Adaptive Control Software (Hauge and Stølen, 2011) S10 -Re-engineering legacy Web applications into RIAs by aligning modernization requirements, patterns and RIA features (Conejero et al, 2013) . A detailed view of the conduction phase: automatic search, duplicate study exclusion, study selection, data extraction, snowballing, and data synthesis.…”
Section: Selection Of Primary Studiesmentioning
confidence: 99%
“…-Okubo et al [57] propose a method for security impact and security requirements analyzes. There are two types of security impact described with more details in the paper: horizontal impact on artifacts in the same stage and vertical impact on artifacts in a later stage.…”
Section: Patterns Not Modelsmentioning
confidence: 99%
“…The method proposed by Okubo et al [57] makes use of security requirements patterns and security design patterns.…”
Section:  Not Modelsmentioning
confidence: 99%